2012
DOI: 10.5402/2012/657979
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aquatic and Land-Based Training on the Metabolic Cost of Walking and Motor Performance in Children with Cerebral Palsy: A Pilot Study

Abstract: Aim. To evaluate the effects of aquatic (AQ) compared to a land-based (LB) intervention programs on metabolic cost of walking (MCW), gross motor function and locomotor performance in children with cerebral palsy (CP). Methods. Eleven children with spastic diplegic CP completed this study, six in the AQ (5.2 ± 1.45 yrs) and five in the LB group (4.1 ± 1.33 yrs). MCW derived from Oxygen uptake (VO 2 ) measured with a Cosmed K4 device and walking speed at steady state. Additional measures included the 10-m test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 47 publications
1
18
0
10
Order By: Relevance
“…Swimming is a community-based exercise that is believed to be fun, not to increase pain during exercise and not to increase the risk for injury in youth with CP, [17][18][19] but so far no randomized controlled trial has been published to support this. Swimming and other aquatic interventions have been reported to have a positive effect on gait velocity 18,20 and aquatic skills. [17][18][19] Kelly et al 21 reported that fatigue was not significantly increased after a 12-week community aquatic exercise program.…”
Section: Introductionmentioning
confidence: 99%
“…Swimming is a community-based exercise that is believed to be fun, not to increase pain during exercise and not to increase the risk for injury in youth with CP, [17][18][19] but so far no randomized controlled trial has been published to support this. Swimming and other aquatic interventions have been reported to have a positive effect on gait velocity 18,20 and aquatic skills. [17][18][19] Kelly et al 21 reported that fatigue was not significantly increased after a 12-week community aquatic exercise program.…”
Section: Introductionmentioning
confidence: 99%
“…Não foram revelados efeitos de interação entre os fatores grupo e tempo do escore do GETZ et al, 2012;GETZ;VERMEER, 2007;JORGIC et al, 2012) BORGER, 1993;GILBERG;GILBERG;GROTH, 1989;LOSSE et al, 1991) podendo interferir negativamente no seu desenvolvimento e em sua qualidade de vida (ENGEL-YEGER;KASIS, 2010;LIBERMAN;RATSON;BART, 2013;MISSIÚNA et al, 2007;RIVILIS et al, 2011;SIGMUNDSSON et al, 1998;TAL-SABAN et al, 2012;WAGNER et al, 2012;ZWICKER;HARRIS;KLASSEN, 2012). Portanto, os resultados encontrados no presente estudo são um alerta, pois reforçam que sem intervenção, a distância do percurso de desenvolvimento das crianças TDC em relação àquele da criança típica pode seguir pela adolescência e também pela vida adulta KOOISTRA;LARKIN, 2001;HENDERSON;HENDERSON, 2002;MISSIÚNA et al, 2007;TAL-SABAN et al, 2012;TAYLOR;FAYED;MANDICH, 2007).…”
Section: Escore Total Do Questionário De Professoresunclassified
“…Por outro lado, os efeitos da intervenção no meio aquático em crianças portadoras de necessidades especiais (paralisia cerebral, autistas e deficientes visuais) tem sido objeto de estudo frequente. De forma geral, os resultados destes estudos indicam que o meio aquático favorece o desenvolvimento e potencializa os resultados de programas de intervenção voltados a crianças que apresentam prejuízos motores (DIMITRIJEVIC et al, 2012;DORVAL;TETREAULT;CARON, 1996;FRAGALA-PINKHAM;HALEY;O'NEIL, 2008;GETZ et al, 2012;GETZ;VERMEER, 2007;PAN, 2010;. Os autores argumentam que o meio aquático além de oferecer um ambiente seguro, divertido, motivante e propício às interações sociais, possui , 1996;HILL, 2001;MISSIÚNA;BARTLETT, 2006;SCHAFER et al, 1989).…”
Section: Introductionunclassified
See 2 more Smart Citations